2019
DOI: 10.1038/s42255-019-0152-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of human adipose tissue identifies depot- and disease-specific cell types

Abstract: The complex relationship between metabolic disease risk and body fat distribution in humans involves cellular characteristics which are specific to body fat compartments. Here we show depotspecific differences in the stromal vascual fraction of visceral and subcutaneous adipose tissue by performing single-cell RNA sequencing of tissue specimen from obese individuals. We characterize multiple immune cells, endothelial cells, fibroblasts, adipose and hematopoietic stem cell progenitors. Subpopulations of adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
351
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(386 citation statements)
references
References 65 publications
34
351
1
Order By: Relevance
“…The ASC lineage (marked by PDGFRA and DCN) (Guerrero-Juarez et al, 2019), including c0, c1, c3 and c5, accounted for a large proportion (49.2%) of the SVF ( Figure 1C), which is comparable with that (55%) reported previously (Vijay et al, 2020). A large and diverse population of immune cells (49.9%) were found, including both myeloid cells and lymphocytes.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The ASC lineage (marked by PDGFRA and DCN) (Guerrero-Juarez et al, 2019), including c0, c1, c3 and c5, accounted for a large proportion (49.2%) of the SVF ( Figure 1C), which is comparable with that (55%) reported previously (Vijay et al, 2020). A large and diverse population of immune cells (49.9%) were found, including both myeloid cells and lymphocytes.…”
Section: Resultssupporting
confidence: 84%
“…Next, we found that the four subpopulations had distinct expression profiles ( Figure 3B; Table S3). Cluster c0 expressed high levels of adipose stem cell or preadipocyte markers such as CXCL14, APOD, APOE, MGP and WISP2 (Vijay et al, 2020). The gene signature of c0 was enriched with the Gene Ontology (GO) term "positive regulation of hemostasis" (representative genes: CD36, F3 and SELENOP; Figure 3C).…”
Section: Heterogeneity Of Ascs In the Svf Of Adipose Tissue Unraveledmentioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate that the ASC population is naturally occurring in the normal adipose tissue of all types, we referred to recent results from single-cell analysis of general human adipose tissue (31). We found that one of the identified clusters (P5, table s2 of the paper 31 Therefore, to investigate the continuous transition of ASCs to COL11A1-expressing CAFs, we partitioned the 34 pancreatic samples into three groups, considering whether the corresponding attractor includes COL11A1 among the top 100 genes.…”
Section: Dominant Fibroblastic Population In the Normal Pancreatic Samentioning
confidence: 99%